Recurrent Pneumonia With Tuberculosis and Candida Co-infection Diagnosed by Metagenomic Next-Generation Sequencing: A Case Report and Literature Review - Ma, Ning; Chen, Mei; Ding, Jingyi; Wang, Fang; Jin, Jingbo; Fan, Sitong; Chen, Jiajia (Frontiers in Medicine, 2022)
A 82-year-old male patient was hospitalized in the Respiratory Department for "repeated cough and shortness of breath for 10 years, recurrence worsened for 1 month". Later, he was transferred for further diagnosis and treatment, to the Infectious Disease Department for further hospitalization. Previously, the patient had repeatedly undergone tuberculosis-related examinations including bronchoscopy examinations. However, no evidence of MTB infection was found. Early anti-infection treatments failed. Due to repeated symptoms, we performed bronchoscopy again and sent alveolar lavage fluid for mNGS test. Subsequently, MTB and Candida albicans were detected by mNGS. After anti- tuberculosis and anti-fungal treatments, the symptoms were significantly relieved, and the chest CT showed resolution of the lung lesions. Therefore, we successfully diagnosed and treated a case of recurrent pneumonia with tuberculosis and candida co-infection diagnosed by mNGS